The Death of Authentic Language Learning Assessment in Indonesia During The Global Pandemic - Siti Maria Ulfa M; Rezki Suci Qamaria (PTK: Jurnal Tindakan Kelas, 2021)
This article aims to discuss the implementation of authentic language learning assessment in Indonesia during the global pandemic. In the 2013 curriculum, the result of the learning process requires an authentic assessment because it has high relevance to a scientific approach of learning that meets the demands of the curriculum. However, authentic assessment has faced serious challenges in the process of its implementation during the COVID-19 pandemic that has hit globally since 2019. In this case, teachers face major challenges in the assessment process including in learning foreign languages, especially English subjects. The assessment system in the language learning process during the pandemic is demanded to be more flexible therefore government must consider a solution. The solution is expected to open up opportunities for teachers to modify the authentic assessment system to an alternative assessment as an adjustment during the global crisis.